Control-theoretic integration of stimulation and electrophysiology for cognitive enhancement - Singh, Matthew F.; Cole, Michael W.; Braver, Todd S.; Ching, ShiNung (Frontiers in Neuroimaging, 2022)
Transcranial electrical stimulation (tES) technology and neuroimaging are increasingly coupled in basic and applied science. This synergy has enabled individualized tES therapy and facilitated causal inferences in functional neuroimaging. However, traditional tES paradigms have been stymied by relatively small changes in neural activity and high inter-subject variability in cognitive effects. In this perspective, we propose a tES framework to treat these issues which is grounded in dynamical systems and control theory. The proposed paradigm involves a tight coupling of tES and neuroimaging in which M/EEG is used to parameterize generative brain models as well as control tES delivery in a hybrid closed-loop fashion. We also present a novel quantitative framework for cognitive enhancement driven by a new computational objective: shaping how the brain reacts to potential “inputs” (e.g., task contexts) rather than enforcing a fixed pattern of brain activity.